Manajemen Pelayanan Publik Pada Pelaksanaan Program E-Ktp - Rafa Abiyanu Pasya; Maulana Rifa'i; Dewi Noor Azijah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Public service management is a step in managing various aspects of the process of preparing and providing goods and services to the community. In this case, public service becomes one of the important roles in a system of governance where with the existence of this public service the service system to the community can run effectively and efficiently.